Sitona Germar 1817 (Coleoptera: Curculionidae) Species, Distributions and Population Developments in Alfalfa (Medicago sativa L.) Cultivated Areas: Turkey, Iğdır Province Alfalfa Areas - Celalettin GÖZÜAÇIK; Neslihan GÜLTEKİN; Antonio J. VELÁZQUEZ DE CASTRO (Türkiye Tarımsal Araştırmalar Dergisi, 2021)
This study was conducted to determine alfalfa (Medicago sativa L.) pest species of Sitona Germar (Coleoptera: Curculionidae) in Iğdır Province located in the Eastern Anatolia Region of Turkey where alfalfa was cultivated in the years 2019 and 2020. Field surveys were carried out at 39 locations between April and November, and 6.107 adult individuals were collected from 64 fields using sweeping nets. Based on research results, six species Sitona humeralis Stephens, 1831, S. concavirostris Hochhuth, 1851, S. bicolor Fåhraeus, 1840, S. longulus Gyllenhal, 1834, S. callosus Gyllenhal, 1834 and S. puncticollis Stephens, 1831 (Coleoptera: Curculionidae) were identified. Of these species, S. humeralis was found as the most intense and dominant species with a rate of 81.4%. The density rates of other species were detected as 12.1%, 5.0%, 1.1%, 0.3% and 0.1%, respectively. It was determined that the adults of Sitona species populations reached the highest number in July and October, and S. humeralis was the most intense and widespread species.